Richter's type of obturator hernia with Howship Romberg sign: a case report - Gayathre, S. P.; Kudiyarasu, M.; Saugunan, Bala Brindha; Kannan, R. (International Surgery Journal, 2021)
Obturator hernia is a rare type of pelvic hernia in which intraperitoneal contents protrude through the obturator foramen and is most commonly found in females. It accounts for about 1% of all abdominal hernias and possesses a great diagnostic challenge due to the non-specific symptoms and meagre clinical signs. Hereby we report a case of obturator hernia in an nonagenarian emaciated fragile old lady who presented with features of acute Intestinal obstruction and was diagnosed using computed tomography as right sided obturator hernia and eventually was taken up for emergency laparotomy. The herniated segment was resected and anastomosis was done with primary closure of the defect. Postoperative period was uneventful and the patient was discharged on postoperative day 7.